San Marino : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation for San Marino reports that the economy has slowed considerably since 2000 with the fading of key competitive advantages that had contributed to past rapid development. To restore a positive net asset position and the ability to buffer adverse external shocks, the authorities aim at maintaining the budget in balance or in surplus over the medium term while preserving tax rate advantages. To sustain fiscal consolidation with unchanged or lower tax rates, remaining tax administration problems need to be addressed and generous entitlement programs reformed.